2013
DOI: 10.1002/cncr.28129
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of older patients with acute myeloid leukemia

Abstract: BACKGROUND Acute myeloid leukemia (AML) is the common form of acute leukemia in adults, accounting for over 80% of all acute leukemia in those over the age of 18 years. Overall 5-year survival remains poor in older AML patients; it is less than 5% in patient over 65 years. We examined whether survival has improved for subsets of geriatric AML patients over three successive decades. METHODS Surveillance, Epidemiology, and End Results (SEER) data were used to determine trends in relative survival by age among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(109 citation statements)
references
References 34 publications
3
105
0
1
Order By: Relevance
“…AML accounts for ~80% of all acute leukemia cases in adults, and the incidence of this disease has been revealed to increase with age (2,3). At present, AML is curable in 35-40% of patients <60 years old; however, among patients >60 years of age, cases of full recovery are less common (5-15%) (1,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AML accounts for ~80% of all acute leukemia cases in adults, and the incidence of this disease has been revealed to increase with age (2,3). At present, AML is curable in 35-40% of patients <60 years old; however, among patients >60 years of age, cases of full recovery are less common (5-15%) (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…At present, AML is curable in 35-40% of patients <60 years old; however, among patients >60 years of age, cases of full recovery are less common (5-15%) (1,4). Due to the fact that survival rates remain relatively low (overall 5-year survival is <5% in older patients), novel therapeutics and treatment strategies are required (3).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics of elderly patients with AML differ from those of younger patients, with poorer survival and treatment outcomes (34). Surveillance, epidemiology and end results data demonstrated that the overall 5-year survival was <5% in patients aged >65 years of age (35); however, those patients who received high-dose chemotherapy exhibited improved outcomes (34). In the current study, more changeable hypomethylation was observed in elderly patients (particularly patients with M2 subtype AML) than in younger patients, which may facilitate the elucidation of age-associated variations in clinical treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MDS, AML incidence increases with advancing age, with incidence rates in the U.S. and Europe of 10 per 100,000 persons or higher for patients aged $65 years [14,15]. AML has a poor prognosis, particularly in older patients and those with adverse disease characteristics (e.g., secondary AML, complex cytogenetic abnormalities, or FLT3 mutation) [26][27][28][29][30]. Three-quarters of patients with AML die within 5 years of diagnosis, and survival decreases with increasing age [26].…”
Section: Introductionmentioning
confidence: 99%
“…AML has a poor prognosis, particularly in older patients and those with adverse disease characteristics (e.g., secondary AML, complex cytogenetic abnormalities, or FLT3 mutation) [26][27][28][29][30]. Three-quarters of patients with AML die within 5 years of diagnosis, and survival decreases with increasing age [26]. Disease characteristics and performance status are closely considered when evaluating patient eligibility for treatment with intensive therapies (e.g., induction followed by consolidation chemotherapy or stem cell transplant [SCT]) versus low-intensity options such as injectable azacitidine or decitabine [27][28][29][31][32][33].…”
Section: Introductionmentioning
confidence: 99%